A four-microRNA panel in serum may serve as potential biomarker for renal cell carcinoma diagnosis - Li, Rongkang; Chen, Wenkang; Lu, Chong; Li, Xinji; Chen, Xuan; Huang, Guocheng; Wen, Zhenyu; Li, Hang; Tao, Lingzhi; Hu, Yimin; Zhao, Zhengping; Chen, Zebo; et al. (Frontiers in Oncology, 2023)
Background: Renal cell carcinoma (RCC) is one out of the most universal malignant tumors globally and the incidence increasing annually. MicroRNA (miRNA) in serum could be considered as the non-invasive detecting biomarkers for RCC diagnosis. Method: 224 participants (112 RCC patients (RCCs) and 112 normal controls (NCs)) were enrolled in the three-phrase study. RT-qPCR was applied to reveal the miRNAs expression levels in RCCs and NCs. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were utilized for predicting the diagnostic ability of serum miRNAs for RCC. Bioinformatic analysis and survival analysis were also included in our study. Results: Compared to NCs, expression degree of miR-155-5p、miR-224-5p in serum were up-regulated in RCC patients significantly, and miR-1-3p, miR-124-3p, miR-129-5p, miR-200b-3p were down-regulated. A four-miRNA panel was construed and the AUC of the panel was 0.903 (95% CI: 0.847 - 0.944; p< 0.001; sensitivity = 75.61%, specificity = 93.67%). Results from GEPIA database indicated that CHL1，MPP5 and SORT1 could be seen as promising target genes of the four-miRNA panel. Survival analysis of candidate miRNAs manifested that miR-155-5p was associated with the survival rate of RCC significantly. Conclusions: The four-miRNA panel in serum has a great potential to be non-invasive biomarkers for RCC sift to check.